Art and Architecture Under Poonjar Palace - Najmi V N (IJELLH, 2019)
The study entitled “Art and Architecture under Poonjar Palace” discussed about the royal patronage of Art and Architecture under the rajas of poonjar. Palace and its temples included simple Kerala art and Kerala style of Architecture. The famous mangaladevi temple once a part of the Royal Family. Mangaladevi alias Kannaki is their family deity.